Individual and combined effects of antioxidant and salinity on germination characters of rice - A.E. Sharief, A.A. Kandil; Fatah, Fatma M. Abd EL- (Journal of Ecobiotechnology, 2019)
A germination experiment was carried out in rice to study the role played by various antioxidants on germination parameters under salt stress in some rice cultivars. The results indicated that the highest germination percentage, rate (days), index and speed were recorded in Sakha 106 cultivar. An increase in the concentration of salt from 100 mM to 300 mM resulted in a reduction in these parameters. Pretreatment of the seeds with Humic acid at 500ppm increased these studied parameters. All studied characters were affected by the interaction between rice cultivars, salinity concentrations and antioxidants. In general, the study suggested that antioxidant pretreatment in rice seeds can be considered as a potential tool to enhance germination parameters under salinity stress, especially in rice Sakha 106 cultivars.